Síntese de novos azóis derivados da 1,1- difenilacetona - Friedein, Alynne Alegre Souto (2014)
This work describes an efficient method to obtaining new heterocycles from the reaction of acetalization of the ketonic carbonyl, followed by acylation of the enolether, generated in situ from the acetal derivative of 1,1-diphenylacetone, with trifluoroacetic anhydride, tricloroacetila of chloride, clorodiflúoracético anhydride, pentaflúorpropiônico anhydride in the absence of solvents. There were performed reactions of cyclocondensation between 1,1,1-trialo-4-alkoxy-3-alquen-2-ones and hydroxylamine hydrochloride, forming, in general, the 5-trialometil-5-hydroxy-4,5-diidroisoxazóis. To obtaining pyrazoline compounds, was proposed the cyclocondensation between the β-ketones alcoxivinil (ou é β-alcoxivinil ketones?) and four different dinucleophiles: monohydrate hydrazine, phenylhydrazine, thiosemicarbazide and aminoguanidine carbonate. All compounds synthesized on this work, since the acetal to the final heterocycles are inedited and their structures were confirmed by RMN 1H e 13C data. In this work, were also performed antimicrobial activity tests of some compounds against microorganisms, wherein some showed significant result for bacteria of great clinical interest, Staphylococcus aureus.